2006
DOI: 10.1366/000370206777887107
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescence of Erythrosin B as a Robust Probe of Molecular Mobility in Amorphous Solid Sucrose

Abstract: Luminescence from the triplet probe erythrosin B (tetra-iodo fluorescein, Ery B) provides spectroscopic characteristics such as lifetime and emission energy that are sensitive to molecular mobility of the local environment in amorphous solids. This study investigated how variations in the local concentration of Ery B free acid as well as the presence of the dispersing solvent affect the spectroscopic measurements of solid matrix properties (the free acid of Ery B is poorly soluble in water and thus must be int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Previous spectroscopic studies have demonstrated that Ery B is dispersed throughout the sugar matrix and does not aggregate at the concentrations used in this study [33,53]. At a dye/sugar mole ratio of ∼ 0.8:10 4 , each probe is on average surrounded by a matrix shell ∼ 10-11 sugar molecules thick.…”
Section: Resultsmentioning
confidence: 86%
“…Previous spectroscopic studies have demonstrated that Ery B is dispersed throughout the sugar matrix and does not aggregate at the concentrations used in this study [33,53]. At a dye/sugar mole ratio of ∼ 0.8:10 4 , each probe is on average surrounded by a matrix shell ∼ 10-11 sugar molecules thick.…”
Section: Resultsmentioning
confidence: 86%
“…Previous work has established that Ery B does not aggregate under these conditions and reports the mobility of the unperturbed sucrose matrix. 13,29 The data on the sucroseNaCl matrix reported here have been published as part of a more extensive study of the effect of NaCl on sucrose matrix mobility; 28 they are included here for the sake of comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Data were fit to a stretched exponential, or Kohlrausch-Williams-Watts (KWW) decay model, 44 which has been used to fit the intensity decays of Ery B dispersed in a wide variety of amorphous solid sugars 21,26,32,33,[37][38][39][40] and proteins 23,34-36 :…”
Section: Methodsmentioning
confidence: 99%
“…20,21 At this state of minimal perturbation, phosphorescence of Ery B emission is sensitive both to the motions of molecules in its immediate environment 19,20 and to the permeability of oxygen. 22,23 From the excited triplet state, a molecule can return to the ground singlet state either by emission of a photon (phosphorescence) or by one of two non-radiative pathways, matrix-induced deactivation or oxygen quenching.…”
Section: Introductionmentioning
confidence: 99%